Hukum Lingkungan dan Pertanggungjawaban Strict Liability dalam Sistem Hukum Common Law (Studi Kasus Cambridge Water Co. Ltd v. Eastern Countries Leather Plc) - Mahfud Mahfud (Universitas Syiah Kuala, 2010)
ABSTRACT: The possibilities for pollution control still offered today Blackburn J.’s celebrated rule of strict liability, now almost 130 years old, has ensured its continuing popularity. There can be few tort lawyers, however, who have not increasingly wondered how much time should be devoted to a case which has received little judicial attention in recent years, and which was last subjected to detailed consideration by the House of Lords nearly 50 years ago, until, that is, the much-published decision of the House of Lords in Cambridge Water Co. Ltd v. Eastern Countries Leather Plc. (Environmental Law and The Strict Liability Application In the Common Law System) (The Case Study of Cambridge Water Co. Ltd V. Eastern Countries Leather Plc)